The biodynamics of knowledge creation : an archaeological, behavioural and neurological account of the creation of human knowledge - Christie, Warren James Alexander (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Information Science))--Stellenbosch University, 2008.